Choose Test Assessment Effectiveness of Left - Hand Cup Technique for Male Hanoi Shuttlecock Athletes - Truong, Nguyen Cong (International Journal of Humanities and Education Development (IJHED), 2022)
Using routine methods, 8 tests were selected to evaluate the attack efficiency with the left-hand cup technique for male Hanoi shuttlecock athlete with sufficient reliability after 2 tests, and at the same time determined that there was a relationship between the two. strongly correlated with the performance of Hanoi shuttlecock athlete r > 0.789 (probability threshold P < 0.05).